2018
DOI: 10.1007/s00268-018-4534-9
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Indocyanine Green Fluorescence‐Guided Video‐Assisted Technique for Sentinel Node Biopsy in Breast Cancer

Abstract: Video-assisted ICG-guided technique is a feasible and surgeon-friendly method for SLN biopsy, with equivalent efficacy compared to RI, providing an accurate staging of the axilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…This study gives insight into ICG with MB as a viable alternative for accurately mapping the lymphatics prior to axillary lymph node surgery. Furthermore, the findings of this study, along with other studies have shown that the use of ICG lymphography is an additional, reliable method to evaluate the upper extremity lymphatic drainage of those patients with clinically evident BCRL [93][94][95][96][97] . ICG lymphography can detect lymphatic channels up to 2 cm deep from the surface of the skin and can show lymphatic channels, lymphatic valves, and lymphatic flow immediately after injection of ICG [98] .…”
Section: Stagementioning
confidence: 52%
“…This study gives insight into ICG with MB as a viable alternative for accurately mapping the lymphatics prior to axillary lymph node surgery. Furthermore, the findings of this study, along with other studies have shown that the use of ICG lymphography is an additional, reliable method to evaluate the upper extremity lymphatic drainage of those patients with clinically evident BCRL [93][94][95][96][97] . ICG lymphography can detect lymphatic channels up to 2 cm deep from the surface of the skin and can show lymphatic channels, lymphatic valves, and lymphatic flow immediately after injection of ICG [98] .…”
Section: Stagementioning
confidence: 52%
“…The limitations of both dye and radioisotope (RI) mapping has led to the development of new contrast agents for sentinel node biopsy, such as magnetic 19,20 and fluorescence imaging approaches. [21][22][23][24][25][26][27][28][29][30][31] Fluorescence imaging was first used clinically in the 1940 s, when fluorescein was used in the presence of ultraviolet (UV) light to delineate suspected brain tumors. 32 Fluorescence imaging with currently approved exogenous fluorophores is a safe, non-ionizing and rapid technique, with macroscopic visualization capabilities to facilitate surgical guidance, as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With OLLI, nuclear medicine employees and lymphoscintigraphy are not required for detection of SNL’s by ICG. OLLI is likely to cost less than ROLL as ICG only costs 65 euros, excluding tax per patient . Spillage of fluorescent dye was already reported in previous study .…”
mentioning
confidence: 56%